2008
DOI: 10.5483/bmbrep.2008.41.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of silk protein sericin against hydrogen peroxide-induced oxidative stress in skin fibroblasts

Abstract: The antioxidant potential of silk protein sericin from the non-mulberry tropical tasar silkworm Antheraea mylitta cocoon has been assessed and compared with that of the mulberry silkworm, Bombyx mori. Skin fibroblast cell line (AH927) challenged with hydrogen peroxide served as the positive control for the experiment. Our results showed that the sericin obtained from tasar cocoons offers protection against oxidative stress and cell viability is restored to that of control on pre-incubation with the sericin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 35 publications
11
110
0
2
Order By: Relevance
“…It has been shown that sericin has a strong antioxidant activity that suppresses lipid peroxidation and inhibits tyrosinase activity (Kato et al, 1998). Dash et al (2008) demonstrated that sericin prevented oxidative stress in a skin fibroblast cell line when exposed to hydrogen peroxide and inhibited the production of intracellular hydrogen peroxide in keratinocytes. Our group has recently reported that sericin increased the preimplantation development and quality of bovine embryos produced in vitro and reduced the oxidative stress exerted by hydrogen peroxide on embryos in culture (Isobe et al, 2012).…”
mentioning
confidence: 99%
“…It has been shown that sericin has a strong antioxidant activity that suppresses lipid peroxidation and inhibits tyrosinase activity (Kato et al, 1998). Dash et al (2008) demonstrated that sericin prevented oxidative stress in a skin fibroblast cell line when exposed to hydrogen peroxide and inhibited the production of intracellular hydrogen peroxide in keratinocytes. Our group has recently reported that sericin increased the preimplantation development and quality of bovine embryos produced in vitro and reduced the oxidative stress exerted by hydrogen peroxide on embryos in culture (Isobe et al, 2012).…”
mentioning
confidence: 99%
“…이와 같은 부작용을 완화시키 기 위한 방편으로 친환경 소재 개발 연구가 진행되고 있 으며 특히, 여러 천연 물질들의 미백, 항산화, 항균, 보습 효과 등이 과학적으로 입증되면서 이들에 대한 연구가 확 대되고 있다 (Mukherjee et al 2011, Choi et al 2010 (Yeo et al 2000, Dash et al 2008, Lee et al 2001 (Zhang et al 2011, Kim et al 2003, Choi et al 2002. (Fig.…”
Section: 서 론unclassified
“…Cell viability was then determined by the same microplate reader at 550 nm and the concentration of H 2 O 2 that resulted in cell damage was obtained. This concentration was then applied to NHF cells (8 × 10 3 cells/well) for 24 h. After treatment, the cells were incubated with the extracts (5 and 10 μg/ mL) for another 24 h. Determination of cell viability was conducted as described in cytotoxicity against a NHF cell culture section (Dash et al, 2008).…”
Section: Cellular Oxidative Damage Treatmentmentioning
confidence: 99%
“…Cytotoxicity in NHF cells was determined using a method described by Dash et al (2008). NHF cell lines obtained from the National Nanotechnology Center were incubated at 37°C in a chamber containing 5% CO 2 .…”
Section: Cytotoxicity Against a Normal Human Fibroblast (Nhf) Cell Cumentioning
confidence: 99%
See 1 more Smart Citation